A Transcriptomic Analysis Reveals Diverse Regulatory Networks That Respond to Cold Stress in Strawberry (Fragaria×ananassa) - Yong Zhang; Yunting Zhang; Yuanxiu Lin; Ya Luo; Xiaorong Wang; Qing Chen; Bo Sun; Yan Wang; Mengyao Li; Haoru Tang (International Journal of Genomics)
Strawberry is often subjected to cold stress in temperate regions when insulation measures are not strictly applied in protected cultivation. Cold stress adversely influences plant growth and development by triggering a massive change to the transcriptome. To provide the potential strategies in improving strawberry cold tolerance and give a glimpse into the understanding of the complex cold signaling pathways in plants, this study identified attractive candidate genes and revealed diverse regulatory networks that responded to cold stress in strawberry (Fragaria×ananassa) by a transcriptomic analysis. Totally, there were 2397 differentially expressed genes (DEGs) under cold stress treatment (T1) vs. normal treatment (CK). Of these, 1180 DEGs were upregulated, while 1217 DEGs were downregulated. Functional enrichment analysis showed that DEGs were significantly (adjusted P value < 0.05) overrepresented in six pathways including plant hormone signal transduction, flavonoid biosynthesis, mitogen-activated protein kinase (MAPK) signaling, starch and sucrose metabolism, circadian rhythm, and alpha-linolenic acid metabolism. The cold signaling initiated expression of downstream cold-responsive (COR) genes with cis-acting element ABRE or CRT/DRE in the ABA-independent or ABA-dependent pathway to impel plant defense against the stress. Strikingly, GIGANTEA (gene id 101308922), two-component response regulator-like PRR95 (gene id 101295449), and ethylene-responsive transcription factor ERF105-like (gene id 101295082) were dramatically induced under low-temperature treatment, indicating that they played an important role in response to cold stress in strawberry.